Usaha Meningkatkan Hasil Belajar Bahasa Inggris Aspek Kemampuan Membaca melalui Model Pembelajaran Role Playing Siswa Kelas VII SMP Negeri 21 Mataram - Ilham, Muhamad (Lembaga Yasin AlSys, 2023)
The purpose of this study was to determine the improvement in English learning outcomes in the aspect of reading ability through the Role Playing learning model for Class VII students of SMP Negeri 21 Mataram in the 2022/2023 Academic Year. The subjects of this study were 32 grade VII students of SMP Negeri 21 Mataram, consisting of 15 female students and 17 male students. The stages of this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The results showed that the data on student learning outcomes in learning English experienced an increase from the initial data obtained 62.50%, increased to 81.25% in cycle I, and to 100% in cycle II. So student learning outcomes in English learning conducted by the teacher are very good. Learning planning, there was an increase from 70.00% in cycle I and increased to 85.00% in cycle II. So the lesson planning carried out by the teacher is very good. While the implementation of learning carried out by the teacher also experienced an increase from 75.00% in cycle I to 87.50% in cycle II. So the implementation of learning carried out by the teacher is also very good. Student learning activities increased in cycle I by 67.86%, and became 85.71% in cycle II. Based on the results of the research analysis as explained above, the action hypothesis which states that